RESPON IBU RUMAH TANGGA TERHADAP SAMPAH PLASTIK DI PERUMAHAN CIPTA LESTARI I KELURAHAN SIALANGMUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - Atikah Ulayya; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Waste occupies an important role in the environmental pollution problem in big cities of the world and also Indonesia. Plastic waste is a kind of anorganic waste that generally can not rot. The purpose of this study were to know about the socio-economic conditions of the Housewife, their knowledge about the plastic waste, and their responses about the plastic waste treatment. The research was using descriptive quantitative method by displaying the results in the form of tables and contains the narrative descriptions. The study was conducted in Perumahan Cipta Lestari RT 03 RW 04 Jl. Cipta Karya, SialangMunggu, Tampan, Pekanbaru, Riau Province. The result of this study showed that most of the socio-economic conditions of respondences are work as a Housewife, their last education are senior high school, have decent house to live at, have enough salary for living expenses, and most of them are moslem. Then the result showed that the respondences have pretty good knowledge about the plastic waste and have high response either.Keyword : Plastic waste, Socio-economic condition, Housewife, Plastic waste treatment